Evaluation of Sustainable Transportation in 25 European Countries Using GRA and Entropy MABAC - İbrahim Miraç Eligüzel; Nazmiye Eligüzel (Journal of Transportation and Logistics)
The increasing demand for sustainable transportation systems has driven researchers and policymakers to investigate new methodologies. European countries, with their diverse landscapes and varying population densities, have been particularly focused on optimizing transportation systems under the aim of achieving sustainability goals. This study evaluates the sustainable transportation practices in 25 European Union member countries through the implementation of grey relational analysis (GRA) and the entropy-multi-attributive border approximation area comparison (entropy-MABAC) methodology. The proposed study specifically examines the sustainability of the transportation system in these European countries. Twelve criteria have been established, providing a comprehensive analysis of various aspects of the sustainability of transportation systems. The utilization of GRA and entropy-MABAC methodology offers a robust framework for decision-makers to make informed choices regarding transportation policies and investments, ensuring a more sustainable and efficient future for European transportation systems. The findings rank Sweden and Germany first and second, respectively. Poland ranks last in both. The correlation analysis produced a coefficient of 0.8218, which is near 1 and implies a substantial correlation between the outcomes generated by GRA and entropy-MABAC, indicating that the outputs from both approaches are consistent. The findings indicate that the two methods are reliable and yield similar results.